2007
DOI: 10.1093/jac/dkm078
|View full text |Cite
|
Sign up to set email alerts
|

In vitro effect of the presence of human albumin or human serum on the bactericidal activity of daptomycin against strains with the main resistance phenotypes in Gram-positives

Abstract: Daptomycin exhibited rapid bactericidal activity against the strains of the three Gram-positive species tested, regardless of resistance phenotype or the presence of physiological concentrations of albumin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 8 publications
1
40
0
1
Order By: Relevance
“…Kill rates of amoxicillin were much higher in active serum, too, despite its low protein binding. This disconnect between MICs and kill rates is very well in agreement with previously published data [8,20,[40][41][42][43][44][45][46][47]. Wouldn't it be more conclusive to derive PD measures not from static but from dynamic endpoints like kill-rates [65]?…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Kill rates of amoxicillin were much higher in active serum, too, despite its low protein binding. This disconnect between MICs and kill rates is very well in agreement with previously published data [8,20,[40][41][42][43][44][45][46][47]. Wouldn't it be more conclusive to derive PD measures not from static but from dynamic endpoints like kill-rates [65]?…”
Section: Discussionsupporting
confidence: 89%
“…Likewise, the bactericidal activity of tigecycline was underestimated if Gram-positive and Gram-negative indicator strains were exposed to the calculated free drug level whereas the agent was three-fold more active in the presence of albumin [44]. Although high protein binding of daptomycin (>90%) caused a threeto four-fold increase in MICs and MBCs [45], total daptomycin concentrations in the presence of human albumin or serum were bactericidally active against E. faecium, whereas the calculated free fraction was not [46]. Oritavancin retained bactericidal activity against enterococci in time kill assays although MICs increased up to eightfold in the presence of albumin [47].…”
Section: Introductionmentioning
confidence: 99%
“…However, taking into consideration the rapid emergence of rifampicin resistance when used as monotherapy [23], it that the use of daptomycin in the treatment of S. epidermidis-related infections is more feasible. This is supported by other researchers who reported that, upon sometime of exposure, daptomycin was the most active agent in eradicating S. aureus [23], exhibiting very rapid bactericidal activity against this pathogen [15]. As both S. aureus and S. epidermidis are now among the major nosocomial pathogens, their similar response to these antibiotics is very favorable from the clinical point of view because it is possible to define a relatively broad spectrum therapy.…”
Section: Resultsmentioning
confidence: 53%
“…Cells were harvested by centrifugation (for 10 min at 9,5009g and 4°C), resuspended in TSB, and the suspension was adjusted to an optical density (640 nm) equivalent to 1 9 10 9 cells ml -1 before being used in the subsequent assays. Each stock solution of daptomycin (with calcium supplementation at 50 mg l -1 ) [15,16] and rifampicin was prepared in methanol. It was confirmed that methanol, at the concentration used, had no effect on the growth of the S. epidermidis strains studied.…”
Section: Bacterial Strains and Growth Conditionsmentioning
confidence: 99%
“…PB is one of several factors which can substantially influence the PDs of an antibiotic (9,(46)(47)(48). Similar extents of PB have been shown to differentially affect the antimicrobial activity of highly protein-bound antibiotics (7,9,49,50) and impairment of antimicrobial activity in protein-rich medium may differ between gram-positive and gram-negative pathogens (9). Therefore, the effect of PB on individual pathogens has to be investigated for antibiotics on a case by case base.…”
Section: Protein Binding In In Vitro Studies Of Antimicrobial Activitymentioning
confidence: 99%